Icons: Normativity and Gender Inequalities - Valeria Bucchetti (Rosenberg & Sellier, 2020)
This contribution is aimed at offering a disciplinary viewpoint on the “rules without words” for the purpose of investigating “non-linguistic” normativity from the Communication Design perspective. The intention is therefore to examine how Communication Design shapes social reality through the creation or strengthening of social, normative and tacit rules. The focus of the observation are the non-linguistic expressions, rules, that contribute to the development or maintenance of gender-based social inequalities. Specifically, the observation concerns the forms of schematic representation which permeate everyday life and have an informative and prescriptive function, characterized by a high degree of objectivity and addressed to the whole community - both men and women. The contribution inserts itself within an international framework in which the importance of gender equality is central and reaffirmed by the ONU Agenda 2030 and the Resolution of the European Parliament 2018 (2017/2210(INI)).